Saberes, fazeres e educação patrimonial: a gastronomia na escola - Buriol, Dilce Maria Stochero (2023)
The city of São João do Polêsine is a municipality located in the central part of the Jacuí Valley, in the central region of the state of Rio Grande do Sul, 45 kilometers from Santa Maria. Religiosity, gastronomy and other elements especially linked to the culture of Italian immigrants can be observed in several places in the city, as the municipality belongs to the territory of the former Fourth Imperial Colony of Italian Immigration created in RS. Today, this municipality is part of the Quarta Colônia Municipal Sustainable Development Consortium and its territory belongs, due to the paleontological fossils, to the Quarta Colônia Geopark. With this, this work was carried out with the intention of presenting a teaching program on Heritage Education working with the appreciation and preservation of the gastronomic culture from the tradition of Italian immigrants in the municipality of São João do Polêsine - RS. From this, a notebook was produced with traditional recipes from the region, a product that serves as teaching material in schools and in tourism promotion. From the collection of recipes with the community, they were applied in class with the reproduction of recipes in practices with students from the Municipal Elementary School La Salle and the Municipal Elementary School Pedro Paulo Pradella. At the end of the work it was concluded that from what was studied one can have another vision about what Cultural Heritage is, as it does not refer only to old material things, but the memories of knowledge and practices that also have historical significance and are elements local/regional identities. Therefore, the dissertation is inserted in the Area of Concentration and in the Line of Research of History and Cultural Heritage of the Professional Master's Degree of the Program in Cultural Heritage of UFSM.